Investigations into the conversion of ethanol to butadiene-1,3 using CuO/$\protect \text{La}_2\protect \text{O}_3$/$\protect \text{ZrO}_2$/$\protect \text{SiO}_2$ catalyst systems - Makhin, Maxim; Bedenko, Stanislav; Budnyak, Alexey; Dmitriev, Georgy; Zanaveskin, Leonid (Comptes Rendus. Chimie, 2023)
Catalyst systems of the Lebedev reaction from oxides of Zn, Zr, La, Cu and silica gel were investigated. The catalysts were characterized by BET, XRF, XRD, TPD-$\text{NH}_3$ and TPR. The parameters of ethanol to butadiene-1,3 process were determined using ethanol, acetaldehyde and water as raw materials without inert diluents. When using a mixture of ethanol and acetaldehyde as a feedstock, the selectivity of the butadiene-1,3 formation exceeds 60% and its productivity is at least $0.32~\text{g}_{BD}{· } \text{g}_{cat}^{-1}{· }\text{h}^{-1}$. The average butadiene-1,3 yield was over 34% in 8 h. The stability of the CuO/$\text{La}_2\text{O}_3$/$\text{ZrO}_2$/$\text{SiO}_2$ catalyst was evaluated for 5 cycles of 24 h. When using 96% ethanol, the butadiene-1,3 yield decreased from 25.1% to 13.8% during the full cycle. Oxidation regeneration of the catalyst makes it possible to completely restore its catalytic activity.